2022
DOI: 10.1039/d2nr02994d
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-based antitumor drugs and delivery systems from monotherapy to combination therapy

Abstract: Ruthenium complex is an important compound group for antitumor drug research and development. NAMI-A, KP1019, TLD1433 and other ruthenium complexes have entered clinical research. In recent years, the research on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 312 publications
0
13
0
Order By: Relevance
“…The current developments in nano drug delivery systems have focused on ruthenium-nanomedicine in the form of liposome-Ru nanoformulation, Ru–Se nanoparticles, Ru–Au nanocomposites, Ru–Si nanomaterials to obtain the targeted delivery and enhanced therapeutic activity . Very recently, Wang et al summarized the development of carrier nanomedicine, and self-assembly of carrier-free nanomedicine to deliver ruthenium complexes . In our laboratory, we also have developed a Ru­(arene)­metallopolymer-gold nanoconjugate to enhance the in vitro anticancer activity of Ru-arene complex in colorectal cancer cells .…”
Section: Challenges and Chances In Clinical Translation Of Ruthenium ...mentioning
confidence: 96%
See 1 more Smart Citation
“…The current developments in nano drug delivery systems have focused on ruthenium-nanomedicine in the form of liposome-Ru nanoformulation, Ru–Se nanoparticles, Ru–Au nanocomposites, Ru–Si nanomaterials to obtain the targeted delivery and enhanced therapeutic activity . Very recently, Wang et al summarized the development of carrier nanomedicine, and self-assembly of carrier-free nanomedicine to deliver ruthenium complexes . In our laboratory, we also have developed a Ru­(arene)­metallopolymer-gold nanoconjugate to enhance the in vitro anticancer activity of Ru-arene complex in colorectal cancer cells .…”
Section: Challenges and Chances In Clinical Translation Of Ruthenium ...mentioning
confidence: 96%
“…154 Very recently, Wang et al summarized the development of carrier nanomedicine, and self-assembly of carrier-free nanomedicine to deliver ruthenium complexes. 155 In our laboratory, we also have developed a Ru(arene)metallopolymer-gold nanoconjugate to enhance the in vitro anticancer activity of Ru-arene complex in colorectal cancer cells. 156 Also, we found that the cancer cell uptake of the liposome-encapsulated Ru(arene) complex is 20 times enhanced, and the total ROS formation in cancer cells is also significantly increased compared to the nonencapsulated complex.…”
Section: Challenges and Chances In Clinical Translation Of Ruthenium ...mentioning
confidence: 99%
“…Recently, a lot of TMCs, such as Ru (II), Pt (IV), and Rh (III) PSs, as well as Ir (III) and Os (II) complexes, with attractive photobiological properties have been designed and developed for medical treatment drugs [91]. Excitingly, McFarland and coworkers reported the first Ru (II)‐based PS TLD1433 to enter clinical trials, which will enter into a multicenter phase II study for non‐muscle‐invasive bladder cancer [92]. Owing to large Stokes shifts, high ROS efficiency, and high photochemical properties, Ir‐complexes have the potential to be a promising PDT agent.…”
Section: The Acq‐to‐aie Transformation Of Transition Metal Complex‐pssmentioning
confidence: 99%
“…Indeed, in the last decades, a huge number of antiproliferative Ru-based complexes have been subjected to in-depth preclinical studies, and the literature reveals that progress in perspective Ru-based anticancer agents is outstanding (for recent reviews, see refs. [ 1 , 2 , 3 , 4 ]). Primarily, both organic and inorganic Ru(II) and Ru(III) complexes have been, so far, proposed, sharing special electronic and steric features within a wide repertoire of possible chemical ligands and decorations.…”
Section: Introductionmentioning
confidence: 99%